2015
DOI: 10.1242/dev.127969
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-31 modulates skeletal patterning in the sea urchin embryos

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that repress the translation and reduce the stability of target mRNAs in animal cells. microRNA-31 (miR-31) is known to play a role in cancer, bone formation and lymphatic development. However, studies to understand the function of miR-31 in embryogenesis have been limited. We examined the regulatory role of miR-31 in early development using the sea urchin as a model. miR-31 is expressed at all stages of development and its knockdown (KD) disrupts the patterning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 89 publications
(113 reference statements)
1
42
0
Order By: Relevance
“…It has been reported that miR‐31a‐5p negatively regulates skeletogenesis and osteogenesis (Deng, Wu et al., 2013; Jin et al., 2016; Stepicheva, & Song, 2015; Weilner et al., 2016). Previous studies also demonstrated that decreased stemness and increased senescence are the primary causes of declines in osteogenic differentiation of BMSCs (Fehrer, & Lepperdinger, 2005; Zhou et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR‐31a‐5p negatively regulates skeletogenesis and osteogenesis (Deng, Wu et al., 2013; Jin et al., 2016; Stepicheva, & Song, 2015; Weilner et al., 2016). Previous studies also demonstrated that decreased stemness and increased senescence are the primary causes of declines in osteogenic differentiation of BMSCs (Fehrer, & Lepperdinger, 2005; Zhou et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The temporal and spatial distribution of Arf6 were detected with the Arf6 in situ hybridization probe as previously described (Stepicheva et al, 2015; Stepicheva and Song, 2015). Arf6 coding sequence (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…miR‐31 may be one of the most highly abundant miRNAs that is ubiquitously expressed during Strongylocentrotus purpuratus (sea urchin) early development (Song et al, ; Stepicheva and Song, ). The knockdown of miR‐31 in the sea urchin embryos resulted in a range of dose‐dependent phenotypes, including the formation of extra cells and cell clumps in the blastocoel of the embryo, gut widening and reduction of the embryo size, as well as skeletogenesis defects (discussed below) (Stepicheva and Song, ).…”
Section: Mir‐31 Regulates Diverse Processes During Embryonic Developmentmentioning
confidence: 99%
“…The role of miR‐31 in regulating skeletogenesis is not restricted to vertebrates; indeed, this function seems to be a conserved mechanism in invertebrates. miR‐31 is critical for regulation of skeletogenesis in the sea urchin embryo (Stepicheva and Song, ), an echinoderm and a sister group to the chordates (McClay, ). Sea urchin embryos undergo less complex skeletogenesis than vertebrates.…”
Section: Mir‐31 Maintains Bone Homeostasis In the Adult Vertebrates Amentioning
confidence: 99%
See 1 more Smart Citation